İlkokul İkinci Sınıf İngilizce Dersi Bağlamında Dinleme Becerisi Öğretimi: Bir Durum Çalışması - Süleyman Nihat Şad; Merve Karaova (Anı Publishing, 2015)
The main purpose of this study is to analyse, describe, and compare the three cases (a non-native English teacher, a classroom teacher, and a native-speaker English teacher) in terms of teaching English to young learners in general and teaching listening skills in particular within the context of 2nd grade Primary School English Curriculum. In this respect the study was designed based on holistic multiple case study model. In accordance with triangulation strategy, the data were collected using methods of observation, interview, and document analysis. Moreover, a multiple-choice listening test was developed and administered to compare the listening skills of three teachers‟ students. Based on the analysis of the data collected using different methods, similarities and differences were found between three cases in terms of medium of instruction, classroom atmosphere, instructional activities, activities towards improving four language skills (particularly the listening skill) and language areas, measurement and evaluation, and teachers‟ views on the curriculum and course books. Results of the listening test revealed that, based on the total number of correct answers (Max=20), native-speaker English teacher‟s students were the most successful (X̅=15,66), followed by non-native English teacher‟s students (X̅=8,93), whereas classroom teacher‟s students were the least successful (X̅=6,25). It was concluded that the non-native English teacher and native speaker English teacher were rather successful in teaching English to young learners in general and developing listening skills in particular. However, the classroom teacher, who teaches his class English, needs to improve himself in many aspects particularly his English proficiency and pedagogical knowledge about teaching English to young learners.